PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, TIPE INDUSTRI, KEPEMILIKAN TERKONSENTRASI, SEKTOR PERUSAHAAN DAN UMUR LISTING TERHADAP TINGKAT PENGUNGKAPAN PADA WEB-BASED CORPORATE REPORTING - Kurnia Tri Widayanti; Agung Juliarto (Diponegoro Journal of Accounting, 2016)
This study aims to examine the effects of firm size, profitability, industry type, ownership concentration, sector, listing age on the level of web-based corporate reporting disclosure. Disclosure on web-based corporate reporting is the information provided to stakeholders in the form of financial and non financial information on corporate website. Some benefits of web-based corporate reporting disclosure are to provide timely information and reduce asymmetry of information between managers and investors, reduce agency costs and improve management oversight. The population in this study were all publicly listed companies on the Indonesia Stock Exchange (IDX) 2014. Samples were selected based on predetermined criteria which company that has a website and discloses its annual report and has complete data sets. The number of companies used as samples were 407 companies. Regression analysis was used as a main analysis tool.The results of this study find that profitability, industry type and ownership concentration have significant effects on the level of disclosure on web-based corporate reporting. However, this research does not find evidence that company size, sector and listing age effect the level of disclosure on web-based corporate reporting.